Monitoring of pH and temperature of neuropathic diabetic and nondiabetic foot ulcers for 12 weeks: An observational study. Issue 2 (19th May 2018) - Gethin, Georgina; O'Connor, Gerard M.; Abedin, Jaynal; Newell, John; Flynn, Louisa; Watterson, David; O'Loughlin, Aorghus
Abstract: Wound bed assessment is largely reliant on subjective interpretation without recourse to objective tools or biomarkers. The identification of a point of care, reliable biomarker would enhance assessment and ultimately clinical decision making. Two potentially emerging wound biomarkers exist: surface pH and surface temperature. To date, knowledge of their use has been predominantly in wound prevention, in vitro studies and single time measurements. Our objective was to determine surface pH, size, and surface temperature in noninfected, neuropathic foot ulcers at baseline and at 12 weeks. 50 patients (68% [ n = 34] had diabetes) participated. Mean baseline pH of wounds was 6.95 (SD 1.01); temperature 30.91 °C (SD 3.00); and size 0.82 cm 2 (SD 0.61). After 12 weeks, 26% ( n = 13) were lost to follow‐up, 50% ( n = 25) had healed. Of the remaining patients, mean pH was 6.72 (SD 0.54); temperature 30.88 °C (SD 2.97), and size 0.13 cm 2 (SD 0.13). We have provided baseline values for pH and temperature of noninfected, neuropathic diabetic, and nondiabetic foot ulceration. Further studies in a larger cohort are warranted to determine if temperature and or pH are indicative of a healing or nonhealing state.